2008
DOI: 10.1309/uwk3nahv31gfhm3j
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 and Villin Are Useful Markers of Intestinal Metaplasia in the Diagnosis of Barrett Esophagus

Abstract: The identification of intestinal metaplasia (IM) in the esophagus is necessary for the selection of patients with Barrett esophagus (BE) for surveillance. We studied 108 esophageal biopsy and resection specimens, clinically diagnosed as BE, and stained them for CDX2, villin, HepPar-1, and cytokeratin (CK) 7 to investigate sensitivity for identifying IM. H&E-stained sections showed definite goblet cells in 94 cases. CDX2 and villin were positive in all 94 cases. Of 38 cardia- and 9 fundic-type mucosa samples as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
3
20
0
1
Order By: Relevance
“…However, in our hands, the villin and CDX2 expression are tightly coupled. Similar result was reported in BE too (Shi et al, 2008). A recent study found that knockdown of CDX2 in SW480 cells caused a clear down regulation of villin.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…However, in our hands, the villin and CDX2 expression are tightly coupled. Similar result was reported in BE too (Shi et al, 2008). A recent study found that knockdown of CDX2 in SW480 cells caused a clear down regulation of villin.…”
Section: Discussionsupporting
confidence: 86%
“…Ectopic CDX2 expression was believed related with intestinal metaplasia of the stomach, and Barrett's esophagus(BE) in human beings (Eda et al, 2003;Guo et al, 2004;Shi et al, 2008;Tsukamoto et al, 2004). Silberg DG found that the expression of CDX2 in transgenic mice can lead occurrence of IM in gastric mucosa (Silberg et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13][14][15][16][17] Nevertheless, it has been reported that the Barrett esophagus columnar mucosa is 'intestinalized' when examined by immunohistochemical markers of intestinal differentiation, even in the absence of histological evidence of intestinal metaplasia, that is, goblet cells. [18][19][20][21][22][23] Thus supporting the current American College of Gastroenterology guidelines, which require the presence of intestinal metaplasia for the diagnosis of Barrett esophagus. 24 Clinical experience has suggested the presence of two cyto-architectural patterns of Barrett esophagus dysplasia and the terms type 1 and type 2 or adenomatous and non adenomatous (also known as 'foveolar/hyperplastic') akin to gastric dysplasia, have been applied to these patterns.…”
mentioning
confidence: 52%